Methods of Learning Kitab Kuning for Beginners in Islamic Boarding School (Dayah) - Fakhrurrazi Fakhrurrazi; Saliha Sebgag (Nazhruna: Jurnal Pendidikan Islam, 2020)
This article aims to determine the learning objectives of the Kitab Kuning (Books in Arabic Script used in Pesantren/Dayah) for the beginners of Santri Dayah Darul Huda Langsa City, to find out the responses of students in learning the Kitab Kuning for Santri beginners Dayah Darul Huda Langsa City, and to find out implementation of the method of learning the Kitab Kuning for Santri Dayah Darul Huda Langsa City. This article's research method is a descriptive qualitative research method that produces data in the form of written and oral words of the subject under study. This article results are: The purpose of learning the Kitab Kuning in Dayah Darul Huda Langsa City is to improve students' quality in understanding and reading the Kitab Kuning well. The students' response is outstanding in learning the Kitab Kuning as a lesson that students must follow and must be passed according to the minimum standard of a grade determined by the curriculum and teaching of Dayah. The dominant methods used by teachers are the sorogan and bandongan method. The research implication is how students can read the Kitab Kuning correctly and adequately to achieve the learning objectives according to the institution's wishes.